Phodiclinics' acquisition of New Protector : increasing concentration? - Metton, Eulalie (Competition Commission case series., 2016)
In October 2006, executives at the Council for Medical Schemes (CMS) and private hospital group Netcare were eager to hear the Competition Tribunal's decision regarding the acquisition of the New Protector Group hospitals by Phodiclinics. In March 2006, the Competition Commission had recommended to the Tribunal that the transaction be approved without conditions. However, the CMS was concerned that, if the acquisition went ahead, it would increase concentration in the private hospital market and thereby fuel already-unacceptable price increases. This text examines the process and the issues at stake.